Hunger and its associated factors in the western Brazilian Amazon: a population-based study - Mayline Menezes da Mata; José Anael Neves; Maria Angélica Tavares de Medeiros (BMC, 2022)
Abstract Background Hunger affects millions of people worldwide. In the current pandemic scenario of coronavirus Brazil has experienced an epidemic peak of hunger, amplifying existing prepandemic vulnerabilities, mainly in the North Region of the country. The aim of the present study was to investigate the prevalence of food insecurity and its associated factors in homes with children under 5 years of age in an urban area of a municipality of the western Brazilian Amazon. Methods A household survey was conducted with a probabilistic sample of 557 children and their families. Food insecurity (FI) was determined using the Brazilian Food Insecurity Scale. Associations between variables were analyzed based on the prevalence ratio (PR) and respective 95% confidence intervals (CI) calculated through multiple Poisson regression analysis. Variables with a P value < 0.05 after adjustments were considered significantly associated with the outcome. Results A prevalence of 76.5% (CI 1.36-2.67) food insecurity was found among the families in the study; 42.9% had moderate (CI 1.31-2.83) and severe (CI 1.10-1.83) food insecurity. Moderate and severe FI was associated with low family income (P = 0.00), participation in governmental income transfer programs (P = 0.01), and heads of household with less than 7 years of schooling (P = 0.02). Moreover, substantial frequencies of height deficit and being overweight were found among the children. Conclusions The high prevalence of hunger and food insecurity and its associated factors reflects the context of geographic isolation and social exclusion in which these families live, suggesting that a substantial portion of the population under 5 years of age had experienced episodes of hunger in the 90 days prior to the survey. The prevalence of height deficit and being overweight among the children reveals a scenario of epidemiological/nutritional polarization, requiring the formulation of specific public policies for this population.